Hypoxia effect on proliferative activity of cells in orthotopic xenograft of hepatocellular carcinoma of the liver in the experiment - T. M. Kecheryukova; V. S. Trifanov; A. A. Shulga; A. S. Goncharova; S. V. Gurova; E. P. Ulyanova; A. Yu. Maksimov (Южно-Российский онкологический журнал)
Purpose of the study. The purpose of this research was to investigate the effect of in vivo hypoxic conditions on the proliferative potential of HepG2 liver cancer cells.Materials and methods. Human liver cancer cells of the HepG2 line have been cultured. The HepG2 cell suspension was injected subcutaneously into mice in an amount of 5 × 106 to obtain a xenograft. Tumor nodes that had reached the required size were divided into fragments and transplanted into the orthotopic site. Balb/c nude mice with implanted HepG2 liver cancer xenograft were used in this experiment. The mice with tumor implanted in the liver were divided into two groups, intact and hypoxic. Mice from the second group underwent liver blood flow reduction by occlusion of the portal triad for 20 minutes. Tumor nodes were extracted for histological and immunohistochemical staining for proliferation marker Ki-67 on the 4th day after the procedures. The proportion of positively stained cells was calculated, and the results were statistically analyzed using the Statistica 10.0 software.Results. Orthotopic models of liver cancer in Balb/c Nude mice were obtained. Histological and immunohistochemical studies were carried out. Histological analysis showed that hepatocellular carcinoma is characterized by an average degree of differentiation. In the tissues of these xenografts, by using immunohistochemical analysis for the proliferation marker Ki-67, it was possible to identify statistically significant differences between the two groups, i.e. intact and the one with reduction of blood flow. The proportion of immunopositive cells was 65 [65–70] % and 19 [15–25] %, respectively.Conclusion. A tendency to decreased proliferative activity of tumor cells after hepatic blood flow reduction, i.e. hypoxia exposure, was demonstrated. Our data indicate that the proliferative activity of tumor cells is directly related to the microenvironment, and to the hypoxic environment in particular. Further study of the effect of hypoxia on the processes of growth and development of malignant tumors may contribute to a deeper understanding of the biological features of tumors and their treatment.